INFLUENCE OF DIFFERENT ESTRUS SYNCHRONIZATION PROTOCOLS ON FERTILITY AND PLASMA PROGESTERONE IN ANOESTRUS CROSSBRED COWS - BUHECHA, K V; DHAMI, A J; HADIYA, K K; PATEL, M D; PARMAR, S C; KILLEDAR, A (The Indian Journal of Animal Reproduction, 2023)
A study was carried out to evaluate the clinical response and monitor the peripheral plasma progesteroneprofile in 46 postpartum anoestrus crossbred cows(>90 days) treated with standard hormonal protocols Triu-B/PRID, Ovsynch and Heatsynch(n=12 each), keeping untreated anoestrus control (n=10) group and the resultswere compared with normal cyclic control (n=1 0)group. All the cows(100 %) under three protocols exhibitedestrus within mean intervals of 67.00±1.74, 69.83±0.87 and 68.17±1.24 h, respectively, from PGF2a injection.The conception rates obtained at induced estrus in cows under Triu-B, Ovsynch and Heatsynch protocolswere 33.33, 41.66and 33.33 %, respectively. The corresponding overall conception rates of three cycles were50.00, 58.33 and 41.66%, respectively.In untreated anoestrus control group, only 2 cows (20 %) expressedspontaneous estrus with overall conception rate of 20.00%. In normal cyclic control group the conception rates atfirst cycle and overall of 3 cycles were 40.00 and 60.00%, respectively.The overall mean plasma progesteroneconcentrations (ng/ml) found in true anoestruscows on day 0, 7, 9/10 (Al) of treatment and on day 21 post-Alwere 0.85±0.21, 4.80±0.31, 0.58±0.11 and 3.97±1.14, respectively,underTriU-B protocol; 0.58±0.11, 4.55±0.28,1.33±0.48 and 4.03±1.32 under Ovsynch protocol and 0.81±0.22, 5.11±0.75, 0.43±0.06 and 3.10±1.06underHeatsynch protocol.The values on day 7 of treatment and day 21 post-Al were significantly (P
Keywords: Anoestrus; Crossbred cows; Estrus synchronization; Progesterone; Ovsynch; Heatsynch; PRID